Characteristics and Problematics of SMEs in Ponorogo - Dwiati Marsiwi; Asis Riat Winanto; Purwanto Purwanto (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
Small and Medium Sized Enterprises (SMEs) currently have good developments, especially in the food and beverage sector. Even though the area of business is small, it does not need to be underestimated that this business also needs funds/finance. Financial management and reporting for small and medium sized enterprises are often considered difficult. On the other hand, the Indonesian Accountants Association has applied Accounting Standards which are easier to implement in small business actors, namely the Financial Accounting Standards for Small and Medium Sized Enterprises (FAS-SMEs), effective in 2018. This research aims to explore further information about the existence and evaluation of financial management by SMEs. This study also aims to develop a design (model) of financial management procedures that are easily implemented by SMEs and is in accordance with FAS- SMEs. This research is qualitative research with an in-depth interview method. The informants chosen were food and beverage SMEs in Ponorogo Regency. Based on data obtained from 5 informants, then an analysis is carried out with rational interpretation. This study also obtained information from the Ponorogo Perdagkum related to how the role of the government plays in the management of SMEs.Food and beverage business people choose this business field because it is considered to have great potential for profit because food and beverages are their basic needs. i. Financial management at food and beverage SMEs is still very simple, in the form of simple records, not yet differentiating personal assets from the business, so that it is difficult to determine profits. This has the effect of not being able to compile the financial statements of food and beverage SMEs in the Ponorogo Regency according to FAS SMEs.